Phenotypic Variability of The F2 Populations Derived from Crosses Between Local and Introduced Okra Cultivars - P.K. Dewi Hayati; Mairati Mandwi Yld; Sutoyo Sutoyo; M Zaitialia (Green Engineering Society, 2021)
Okra (Abelmoschus esculenthus) is a vegetable plant consumed in immature and tender texture fruits. Crosses of local okra with introduced varieties are carried out to improve the character of the local cultivars. This study aimed to assess the variability of agronomic characters, both quantitative and qualitative characters of various families of the F2 populations and select superior families that can be used to produce new cultivars. The F2 population was derived from inbreeding and selection of the crosses between local okra cultivars with B291 and Ve022 as introduced cultivars. The study used an experimental method with an individual observation. Qualitative characters were described based on the descriptor by IBPGR, while quantitative characters were analyzed using descriptive statistics. Results showed variation in each F2 family in plant height, the number of flowers per plant and the number of fruits per plant, except for SOMB291-16. FOHVE022-8, FOHB291-15, FOHVE022-17, SOMB291-23 and SOMB291-24 families could be selected due to the extended picking time were in line with the increase of fruit quality. A broad variability of quantitative characters was found for all characters, indicating a high opportunity to obtain valuable traits and desirable segregants in F2 populations. Variations in qualitative characters were found in stem color, leaf shape, fruit color and fruit shape. The selection of plants with specific characters could be maintained with inbreeding or self-pollinated desirable segregants.